2011
DOI: 10.1080/02755947.2011.571516
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Some of the Complexity of a Mixed‐Origin Walleye Population in the East Basin of Lake Erie Using a Mark–Recapture Study

Abstract: At least two genetically distinct populations of walleye Sander vitreus reproduce in Lake Erie: one west-basinorigin population and one east-basin-origin population. Each year, some west-basin-origin walleyes migrate to the east basin and create a mixed-origin walleye population. Uncertainties associated with this migratory behavior make it difficult to describe the dynamics of the east-basin-origin population. We used mark-recapture analysis to estimate the dynamics of the east-basin-origin walleye population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 23 publications
3
39
0
Order By: Relevance
“…Using a spatial tag-recovery model and recoveries from a long-term jawtagging study, Vandergoot and Brenden (2014) found that Lake Erie walleyes exhibited age and spatial variability with respect to movement and mortality components. In particular, walleyes in the Lake Erie's western basin were more likely to move to other regions of the lake than eastern basin fish, which was consistent with previous movement studies (Wang et al, 2007;Zhao et al, 2011). Natural mortalities of age-5 and older walleyes were estimated to be lower than those of younger fish in both the lake's western and eastern basins (Vandergoot and Brenden, 2014).…”
Section: Lake Erie Walleye As a Simulation Basissupporting
confidence: 86%
See 2 more Smart Citations
“…Using a spatial tag-recovery model and recoveries from a long-term jawtagging study, Vandergoot and Brenden (2014) found that Lake Erie walleyes exhibited age and spatial variability with respect to movement and mortality components. In particular, walleyes in the Lake Erie's western basin were more likely to move to other regions of the lake than eastern basin fish, which was consistent with previous movement studies (Wang et al, 2007;Zhao et al, 2011). Natural mortalities of age-5 and older walleyes were estimated to be lower than those of younger fish in both the lake's western and eastern basins (Vandergoot and Brenden, 2014).…”
Section: Lake Erie Walleye As a Simulation Basissupporting
confidence: 86%
“…Spatial structuring in the Lake Erie walleye population has been attributed to several factors, including metapopulation dynamics and regional differences in water quality, trophic structure, and incidence of invasive species (Wang et al, 2007;Berger et al, 2012). In addition to functioning as an apex predator (Ryan et al, 2003), walleye support important commercial and recreational fisheries throughout Lake Erie, with fishing activity mostly concentrated in the western and central basins (Roseman et al, 2011;Zhao et al, 2011). Harvest quotas are set annually to promote sustainability of this economically and ecologically important fishery (Roseman et al, 2011).…”
Section: Lake Erie Walleye As a Simulation Basismentioning
confidence: 99%
See 1 more Smart Citation
“…The primary spawning grounds for Lake Erie walleye are in rivers and on mid-lake reef complexes affiliated with the west basin (Busch et al, 1975;Regier et al, 1969). There is evidence of emigration from the west and central basins to the eastern basin (Zhao et al, 2011) and through the Detroit River corridor (Wang et al, 2007).…”
Section: Study Populationmentioning
confidence: 99%
“…For highly mobile species, for example, survey indices of abundance may remain inaccurate because of seasonal or local changes in distribution within and among management units used in population assessments (Gerber et al, 2003;Schwarz and Seber, 1999). Although the knowledge base is growing (e.g., Wang et al, 2007;Zhao et al, 2011), a comprehensive treatment of walleye movement and migratory patterns in Lake Erie and the ensuing impact it has on rational management remains a critical goal. Such information could provide insight into specific factors that affect the timing, extent, and duration of walleye migratory patterns and how they influence abundance indices used in stock assessment.…”
Section: Countrymentioning
confidence: 99%